2022
DOI: 10.7717/peerj.13704
|View full text |Cite
|
Sign up to set email alerts
|

Integrase deficient lentiviral vector: prospects for safe clinical applications

Abstract: HIV-1 derived lentiviral vector is an efficient transporter for delivering desired genetic materials into the targeted cells among many viral vectors. Genetic material transduced by lentiviral vector is integrated into the cell genome to introduce new functions, repair defective cell metabolism, and stimulate certain cell functions. Various measures have been administered in different generations of lentiviral vector systems to reduce the vector’s replicating capabilities. Despite numerous demonstrations of an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 146 publications
0
6
0
Order By: Relevance
“…First, the overexpression and interference salusin-α recombinant plasmids were constructed, after which they were packaged into 293T cells with the creation of overexpression and interference salusin-α lentiviruses for the infection of target cells, with the aim of directly upregulating or inhibiting the expression of salusin-α in cells at the genetic level. In addition, the target gene introduced by lentiviral construction cοuld be stably expressed in cells without disappearing as a consequence of cell division ( 26 , 27 ). Another advantage was that this system also eliminated experimental interference caused by other human factors, rendering it more a more accurate and convenient method for detecting subsequent signal pathway molecules.…”
Section: Discussionmentioning
confidence: 99%
“…First, the overexpression and interference salusin-α recombinant plasmids were constructed, after which they were packaged into 293T cells with the creation of overexpression and interference salusin-α lentiviruses for the infection of target cells, with the aim of directly upregulating or inhibiting the expression of salusin-α in cells at the genetic level. In addition, the target gene introduced by lentiviral construction cοuld be stably expressed in cells without disappearing as a consequence of cell division ( 26 , 27 ). Another advantage was that this system also eliminated experimental interference caused by other human factors, rendering it more a more accurate and convenient method for detecting subsequent signal pathway molecules.…”
Section: Discussionmentioning
confidence: 99%
“…However, their ability to transduce cells tends to be lower than AAVs or other LVs, and their safety profile is not as well characterized. 23,49 And similar to AAV, IDLV's will not sustain durable expression in cells and tissues with high proliferative capacity.…”
Section: Delivery Mechanisms In Gene Addition: Methods and Modalitiesmentioning
confidence: 99%
“…Like AAVs, IDLVs can be designed with homology arms, combining the benefits of targeted gene therapy with lentiviral cargo capacity. However, their ability to transduce cells tends to be lower than AAVs or other LVs, and their safety profile is not as well characterized 23,49 . And similar to AAV, IDLV's will not sustain durable expression in cells and tissues with high proliferative capacity.…”
Section: Gene Therapy: a Promising Therapeutic Approach For Treating ...mentioning
confidence: 99%
“…With more and more antibiotic-resistant bacterial strains emerging in biofilms, bacteriophages could be a powerful means to target the more persistent species while appearing to be safe themselves [ 22 ]. Genomic analyses demonstrated that STP55 has a short latent period and large burst size for hearty antimicrobial activity but lacks any antibiotic-resistance genes, virulence factor genes, or integrases that would permit a phage to integrate or harm the host genome [ 22 , 23 ]. Furthermore, phages are considered to be very consumer-friendly as they meet the qualifications to be labeled organic, kosher, or halal, thus expanding their versatility or reach in the food market [ 24 ].…”
Section: Bacteria Viruses and Fungi To Control Biofilmsmentioning
confidence: 99%